South Africa (International Monetary Fund, 2022)
South Africa's subpar economic performance over the last decade has weakened its macroeconomic fundamentals and social indicators. In response to formidable COVID-19-related challenges, government expenditure surged, and, amid declining revenue, the budget deficit widened significantly. The South African Reserve Bank (SARB) and the Prudential Authority (PA) preserved adequate liquidity conditions and financial-sector stability. The cyclical recovery from the deep contraction has been faster than expected but its strength is unlikely to be sustained. Benign global market conditions have supported asset performance, although term premia are elevated due to fiscal risks. Bank soundness indicators remain solid, but a deepening bank-sovereign nexus raises some concerns
10.5089/9798400200250.002
Keywords: Graue Literatur; State Capture report; IMF South Africa team; U.S. dollar; headline inflation; IMF-World Bank; Africa; Global; COVID-19; Inflation; International Agreements and Observance; International Organizations; Monetary Policy; International Economics; Statistics; Public Finance; Diseases: Contagious; Debt; Debt Management; Sovereign Debt; Health Behavior; Data Collection and Data Estimation Methodology; Computer Programs: Other; General Aggregative Models: General; Price Level; Deflation; Monetary economics; International institutions; Public finance & taxation; Macroeconomics; Infectious & contagious diseases; Econometrics & economic statistics; Currency; Foreign exchange; International organization; Public debt; Money and Monetary Policy; Health; National accounts; Revenue administration; Monetary policy; International agencies; Debts; Public; Communicable diseases; National income; Finance; Statistics; Prices